2015
DOI: 10.1007/s13580-015-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and oxidative stress induced by proton beam in Cymbidium hybrid

Abstract: We investigated the radiation damages caused by two types of proton beam and gamma ray in the Cymbidium hybrid RB001 [(C. sinensis × C. goeringii) × Cymbidium spp.] to characterize proton beam as a new mutagen for Cymbidium mutation breeding. The protocorm-like bodies (PLBs) of Cymbidium hybrid were irradiated with a 45 MeV proton beam [mean linear energy transfer (LET) = 1.461 keV· m -1 ], a 100 MeV proton beam (LET = 0.7306 keV· m -1 ), and gamma ray (LET = 0.2 keV· m -1). The PLBs treated with radiation dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In Pungsannamul, the MDA content increased significantly in response to increasing proton beam dose and the increase at a dose of 316 Gy was 46% compared to the control. Lipid peroxidation is a sign of oxidative damage, and the level of lipid peroxidation can be determined by measuring the MDA content, which is an end-product of lipid peroxidation, and has been used as indicator of plant membrane stress (Kim et al 2015;Lee et al 2015b). Lee et al (2015b) reported that MDA contents increased in response to increasing gamma-ray and proton beam doses, and that Cymbidium irradiated with proton beams at 100 MeV showed higher MDA contents than Cymbidium irradiated with gamma-rays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Pungsannamul, the MDA content increased significantly in response to increasing proton beam dose and the increase at a dose of 316 Gy was 46% compared to the control. Lipid peroxidation is a sign of oxidative damage, and the level of lipid peroxidation can be determined by measuring the MDA content, which is an end-product of lipid peroxidation, and has been used as indicator of plant membrane stress (Kim et al 2015;Lee et al 2015b). Lee et al (2015b) reported that MDA contents increased in response to increasing gamma-ray and proton beam doses, and that Cymbidium irradiated with proton beams at 100 MeV showed higher MDA contents than Cymbidium irradiated with gamma-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation is a sign of oxidative damage, and the level of lipid peroxidation can be determined by measuring the MDA content, which is an end-product of lipid peroxidation, and has been used as indicator of plant membrane stress (Kim et al 2015;Lee et al 2015b). Lee et al (2015b) reported that MDA contents increased in response to increasing gamma-ray and proton beam doses, and that Cymbidium irradiated with proton beams at 100 MeV showed higher MDA contents than Cymbidium irradiated with gamma-rays. In addition, Alikamanoglu et al (2011) reported MDA content of irradiated soybean had similar tendency with that of Pungsannamul.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation breeding is an alternative method used to improve agronomic traits, such as stress resistance, physical parameters of grain, and nutritional value. It is known that ionizing radiation helps overcome the limitations of the chemical treatment so that new mutations can be generated in a short period [ 21 , 22 , 23 ]. There are two forms of ionizing radiation that transfer energy into a substance: non-particulate (gamma and X rays) and particulate (alpha and beta particles, neutrons, and protons).…”
Section: Introductionmentioning
confidence: 99%